Intraoperative Optical Coherence Tomography (OCT)-Guided Femtosecond Laser-Assisted Descemet Membrane Endothelial Keratoplasty (iFAD) - Joshua Lim; Mohammed M. Abusayf; Yu-Chi Liu; Jodhbir S. Mehta (Bioengineering)
We describe retrospectively the indications and outcomes of nine patients who present with varying degrees of deep posterior stromal scarring or endothelial failure following deep anterior lamellar keratoplasty (DALK). These patients underwent a surgical strategy coined Intraoperative Optical Coherence Tomography Guided Femtosecond Laser-Assisted Descemet Membrane Endothelial Keratoplasty (iFAD). This strategy can be used to address suboptimal visual outcomes following primary DALK. Patients undergoing iFAD first had femtosecond laser-assisted trephination of the underlying posterior lamella using the liquid keratoplasty system on the Femto LDV Z8 platform (Zeimer Ophthalmic Systems AG, Port, Switzerland). A Descemet Membrane Endothelial Keratoplasty (DMEK) graft was subsequently transplanted in place of the removed lamella. Out of nine cases, major indications for seven included post-infective, blepharokeratoconjunctivitis (BKC) and deep stromal scarring related to stromal dystrophy. The remaining two had endothelial failure following primary DALK. The main benefits of this surgical approach are (1) Utilization of integrated real-time iOCT on the femtosecond laser platform allows for precise calibration of a wide range of vertical posterior trephination depths (96–329 microns) from the endothelial surface. (2) Femtosecond laser trephination utilizing a non-applanation liquid interface preserves trephination geometries and maximises precision-based surgical outcomes. (3) iFAD is a viable and straightforward technique for surgeons addressing patients who might otherwise require complex surgery to address residual deep stromal scars post-DALK.